1979
DOI: 10.1021/bi00588a033
|View full text |Cite
|
Sign up to set email alerts
|

Suicide inactivation of bacterial cystathionine .gamma.-synthase and methionine .gamma.-lyase during processing of L-propargylglycine

Abstract: L-Propargylglycine, a naturally occurring gamma, delta-acetylenic alpha-amino acid, induces mechanism-based inactivation of two pyridoxal phosphate dependent enzymes of methionine metabolism: (1) cystathionine gamma-synthease, which catalyzes a gamma-replacement reaction in methionine biosynthesis, and (2) methionine gamma-lyase, which catalyzes a gamma-elimination reaction in methionine breakdown. Biphasic pseudo-first-order inactivation kinetics were observed for both enzymes. Complete inactivation is achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 33 publications
6
65
0
Order By: Relevance
“…The dithioerythritol was not transformed in any of the assays conducted (results not shown). Reactions were started by the addition of cell-free extract except when the effect of propargylglycine was tested (26,27). Then, extracts were preincubated with propargylglycine (range of concentrations: 4 -100 M) for 30 min at 37°C before starting the reaction by adding substrate.…”
Section: Preparation Of Extracts and Enzymementioning
confidence: 99%
“…The dithioerythritol was not transformed in any of the assays conducted (results not shown). Reactions were started by the addition of cell-free extract except when the effect of propargylglycine was tested (26,27). Then, extracts were preincubated with propargylglycine (range of concentrations: 4 -100 M) for 30 min at 37°C before starting the reaction by adding substrate.…”
Section: Preparation Of Extracts and Enzymementioning
confidence: 99%
“…Inhibition of MGL by PPG-To better understand the biochemical characteristics of EhMGL, we evaluated effects of DL-propargylglycine (PPG), a potent inhibitor of the ␥-subfamily of PLP-dependent enzymes (46,47), on the recombinant EhMGLs. Activity of both rEhMGL1 and 2 was inhibited by PPG in an irreversible and slow-binding manner (Fig.…”
Section: Table I Products Of L-methionine Degradation By the Amebic Cmentioning
confidence: 99%
“…LMethioninase displays two absorption maxima at 280 nm, as aromatic amino acids containing protein, and at 420 nm due to the internal aldimine linkage of the aldhyde group of pyridoxal phosphate and Ɛ-amino group of lysine N-terminal domain of PLP-enzyme. The absorption spectra of bacterial and fungal L-methioninase (Tanaka et al, 1977, Johnston et al, 1979, El-Sayed, 2011) are typically to other pyridoxal-dependent enzymes (Bertoldi et al, 2002;Saha et al, 2009). The pyridoxal phosphate co-enzyme was dissociate from the apoenzyme by incubation with 10 mM hydroxylamine, giving one peak at 280nm, with disappearance of the 420 nm peak due to the dissociation of the PLP and hydrolysis of the internal aldimine bond.…”
Section: Pegylation Of L-methioninasementioning
confidence: 99%
“…The ratio of A280/420 was decreased from 4.01 to 1.7, upon addition of pyridoxal phosphate (0.2 mM) to the apo-enzyme, indicating the full reconstitution of the active holo-enzyme (El-Sayed, 2011) (Fig.5). Johnston et al (1979) reported that upon freezing and thawing the ratio of A280/420 of Pseudomonas ovalis Lmethioninase was increased from 3.90 to 4.7, due to the dissociation of pyridoxal phosphate. P. ovalis L-methioninase lacks the ability to restore its original activity by dialysis against pyridoxal phosphate (Johnston et al, 1979), while that of Trichomonas vaginalis enzyme restore more than 90 % of its activity by 0.1mM PLP (Lockwood and Coombs, 1991).…”
Section: Pegylation Of L-methioninasementioning
confidence: 99%
See 1 more Smart Citation